Niektóre problemy badań struktury teorii nauczania uczenia się literatury i jej stosunków z innymi teoriami = Some problems of the research into the structure of the literature teaching theory and its relations with other theories - Biłos, Edward (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The actual level of the literature didactics development requires carrying out methodological research into at least four closely interrelated groups of problems: a) the specificity of literature teaching at school, b) the general structure of the teaching literature theory, c) the intra- and inter-theory relations of the discussed theory, d) the role of the integrating and transformating guidance factor in constructing, functioning and putting the didactic theory into practice. However, the assigned tasks cannot be conducted without taking into consideration the postulates of the general theory relation between various theories.
Keywords: dydaktyka literatury